Psychotherapeutic Treatments to Relieve the Symptoms of Obsessive-Compulsive Disorder (OCD): A Review of Clinical Reports - Carneiro, Juliana Margarida; Bertelli, Rosangela (Advances in Social Sciences Research Journal, 2021)
Obsessive-compulsive disorder (OCD) is a psychopathological condition with high prevalence, characterised by the presence of obsessions, compulsions or both and it is known that psychotherapeutic interventions would allow for the relief of some of the OCD’s symptoms. The aim of the present review of clinical reports published between 2014 and 2019 in journals indexed in the Online Library of Knowledge (B-on) was to provide an overview of psychotherapeutic treatments that were put into service, by psychologists or other health professionals, in order to help OCD patients. Considering that clinical reports are so diverse in terms of reported strategies of intervention and of changes in cognitions, symptoms and behaviours, a narrative approach seemed to be better fitted for capturing the psychotherapeutic treatments reported. Results detected the predominance of the cognitive-behavioural approach with strategies and procedures derived from the cognitive-behavioural model of learning.